Abandoned villages in the Tuscia: Proposal for a method to recognize, preserve and restore the identity of sites - Michele Zampilli; Michele Magazzù (ArcHistoR Architettura Storia Restauro: Architecture History Restoration, 2020)
Tuscia is the name given to most of Etruria, including large areas of Tuscany, Lazio and Umbria. This territory, nowadays usually identified with the province of Viterbo, extends north of Rome, located between imaginary geological boundary lines traced by the River Tiber and the Tyrrhenian Sea.